Presence of rare potential pathogenic variants in subjects under 65 years old with very severe or fatal COVID-19 - López-Rodríguez, Rosario; Del Pozo-Valero, Marta; Corton, Marta; Minguez, Pablo; Ruiz-Hornillos, Javier; Pérez-Tomás, María Elena; Barreda-Sánchez, María; Mancebo, Esther; Villaverde, Cristina; Núñez-Moreno, Gonzalo; Romero, Raquel; Paz-Artal, Estela; et al. (Scientific reports, 2022)
Rare variants affecting host defense against pathogens could be involved in COVID-19 severity and may help explain fatal outcomes in young and middle-aged patients. Our aim was to report the presence of rare genetic variants in certain genes, by using whole exome sequencing, in a selected group of COVID-19 patients under 65 years who required intubation or resulting in death (n = 44). To this end, different etiopathogenic mechanisms were explored using gene prioritization-based analysis in which genes involved in immune response, immunodeficiencies or blood coagulation were studied. We detected 44 different variants of interest, in 29 different patients (66%). Some of these variants were previously described as pathogenic and were located in genes mainly involved in immune response. A network analysis, including the 42 genes with candidate variants, showed three main components, consisting of 25 highly interconnected genes related to immune response and two additional networks composed by genes enriched in carbohydrate metabolism and in DNA metabolism and repair processes. In conclusion, we have detected candidate variants that may potentially influence COVID-19 outcome in our cohort of patients. Further studies are needed to confirm the ultimate role of the genetic variants described in the present study on COVID-19 severity.